PENGARUH LATIHAN DOUBLE LEG SPEED HOP TERHADAP POWER OTOT TUNGKAI PADA EKSTRAKURIKULER LOMPAT JAUH PUTRA SMP SANTA THERESIA AIR MOLEK - Evy Yeti Nadia Galama Sihotang; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
The problem in this study is that there is still a lack of long jump ability, especially in leg muscle power, even though the techniques are already quite good, but when doing repulsion, it still needs to be improved. To fix this problem, the authors provide a form of exercise that increases power, especially in the leg muscles, namely the double leg speed hop exercise. The title raised in this study is